Detection by Single-Cell RNA Sequencing of Virally Mediated Skin Diseases - Linda Zhou; Thomas H. Leung (JID Innovations)
Viruses are well-documented agents of specific skin diseases. However, their role and precise mechanism of action in other skin diseases remain unknown. We describe a single-cell RNA-sequencing–based strategy to interrogate human skin biopsies for viral transcripts, permitting detection of viral infection within a sample, single-cell resolution of virally infected cells and identification of subsequent transcriptomic perturbations. We validate our pipeline with 100% sensitivity and specificity by (i) detecting Merkel cell polyomavirus in Merkel cell carcinoma samples, (ii) detecting specific human papillomavirus strains in known human papillomavirus–positive tumors, and (iii) detecting rubella virus transcripts in patients with known rubella-associated granulomas. We identify infection of known and previously unreported cell types and elucidate viral-mediated transcriptional perturbations. In rubella virus–infected cells, we discover macrophage-specific evolution of the rubella virus E1 capsid protein. Finally, we interrogate skin biopsies from many established nonvirally mediated inflammatory skin diseases and do not find consistent evidence of viral infection in any condition. Combining single-cell RNA-sequencing data with virome detection strategies represents a potentially powerful approach to investigate and elucidate virus-mediated gene regulation in health and disease.